PENGARUH LINGKUNGAN KERJA TERHADAP SEMANGAT KERJA KARYAWAN BAGIAN SERVICE PADA PT. UNITED TRACKTOR TBK PEKANBARU - Riyunita Hasanah; Kasmiruddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This study aims to determine the effect of the work environment on employee morale parts service at PT. United Tracktor Tbk Pekanbaru. From the results of this study concluded that the working environment at PT. United Tractor Tbk Pekanbaru simultaneous effect on employee morale parts service for 46.2%, while the remaining 53.8% is influenced by other variables not included in this study. Data obtained from questionnaires and subsequently processed to then be tested using statistical analysis as a simple linear regression analysis, t test, and correlation analysis and determination using SPSS 17. Results of this study showed that the known t (9073)> t table (1.985) and Sig. (0,000) <0.05. That is unacceptable and the hypothesis states that the working environment have a significant effect on morale.Keywords: Work Environment, Morale, Employee Part Service, PT. United Tracktor